Eksistensi Adat Kenduri Laot pada Masyarakat Nelayan di Aceh Bagian Timur - Suriyani, Meta; Anwar, Saiful (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
The existence of kenduri laot in fishing communities in East Aceh Regency as an implementation of laot customs and customary law. Kenduri laot is a traditional ceremony with the concept of friendship based on Islamic law. Kenduri laot is held every year. Kenduri laot is a ceremony before the east or west season ends. However, the current implementation of the kenduri laot in East Aceh Regency is uncertain and has been neglected. So it is carried out every year or every three years or the time is uncertain. The Lhok Panglima Laot who is in charge of implementing, maintaining and supervising the implementation of Laot customs and customary law only provides customary sanctions of warning and advice regarding the laot kenduri to be implemented every year. The obstacle to implementing the kenduri laot is that the fishing community deliberately ignores and puts aside the kenduri laot. Efforts made are to hold deliberations between the District/Lhok Panglima Laot and the fishing community to discuss and preserve the local wisdom of implementing the kenduri laot every year. Then determine sanctions for those who violate the prohibition from going to sea for several days and/or confiscation of fishing catches